Penggunaan Metode Discovery Untuk Meningkatkan Hasil Belajar Siswa Kelas III Materi Pelestarian Makhluk Hidup Di Sekolah Dasar Negeri 2 Tlogowatu Kecamatan Kemalang Semester 1 Tahun Pelajaran 2021/2022 - Ari Susilawati (Universitas Sebelas Maret, 2022)
The research used was two cycles of Classroom Action Research (PTK). The aim of this research is to improve student learning outcomes by applying the discovery method. The subjects of this research were 22 students in class III Semester 1 of the 2021/2022 academic year at SD Negeri 2 Tlogowatu, Kemalang District, Klaten Regency, consisting of 15 male students and 7 female students. By implementing learning improvements from pre-cycle through Cycle I and Cycle II in research. The results of improving learning using the discovery method in science learning material on the Preservation of Living Creatures can increase. This was proven before experiencing improvement, there were only 5 students out of 22 students or only 22.7% who got a score ≥ 70. This result increased in the first cycle by 14 students or around 63.6% who got a score ≥ 70. This result increased in In cycle II there were 22 students or around 100% who got a score ≥ 70. Meanwhile, the average score in the pre-cycle was 57.3 with the application of the discovery method in cycle I increased to 70.5. And the application of the discovery method in cycle II increased to 86.8.